2006
DOI: 10.1016/j.atmosenv.2006.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Acid-catalyzed reactions of hexanal on sulfuric acid particles: Identification of reaction products

Abstract: While it is well established that organics compose a large fraction of the atmospheric aerosol mass, the mechanisms through which organics are incorporated into atmospheric aerosols are not well understood. Acid-catalyzed reactions of compounds with carbonyl groups have recently been suggested as important pathways for transfer of volatile organics into acidic aerosols. In the present study, we use the aerodyne aerosol mass spectrometer (AMS) to probe the uptake of gasphase hexanal into ammonium sulfate and su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 44 publications
2
59
0
2
Order By: Relevance
“…A number of laboratory studies have shown that atmospheric organics, such as carbonyls, can be transformed to higher-MW products via heterogeneous acid-catalyzed reactions between the gas and particle phases (Jang and Kamens, 2001;Jang et al, 2002Jang et al, , 2003aJang et al, , b, 2004Jang et al, , 2005Garland et al, 2006;Liggio and Li, 2006a, b;Iinuma et al, 2007a, b;Gómez-González et al, 2008). These laboratory studies suggest that heterogeneous acid-catalyzed reactions in the particle phase are important mechanisms for SOA formation and that particle acidity has an impact on SOA yield.…”
Section: Interaction Of Atmospheric Organic Compounds With Sulfuric Acidmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of laboratory studies have shown that atmospheric organics, such as carbonyls, can be transformed to higher-MW products via heterogeneous acid-catalyzed reactions between the gas and particle phases (Jang and Kamens, 2001;Jang et al, 2002Jang et al, , 2003aJang et al, , b, 2004Jang et al, , 2005Garland et al, 2006;Liggio and Li, 2006a, b;Iinuma et al, 2007a, b;Gómez-González et al, 2008). These laboratory studies suggest that heterogeneous acid-catalyzed reactions in the particle phase are important mechanisms for SOA formation and that particle acidity has an impact on SOA yield.…”
Section: Interaction Of Atmospheric Organic Compounds With Sulfuric Acidmentioning
confidence: 99%
“…However, in laboratory experiments performed under low humidity conditions these pathways might have contributed to the oligomers observed in simulation chambers (Sadezky et al, 2006). Furthermore, the formation pathways yielding (2001) Aldol condensation products Carbonyls Barsanti and Pankow (2005), Czoschke and Jang (2006b), Garland et al (2006), Liggio and Li (2006a, b), , Tolocka et al (2004b) higher-MW products in the gas phase might very well be involved in new particle formation processes such as nucleation, especially under laboratory conditions. The lower right part of Fig.…”
Section: Chemical Nature and Formation Pathwaysmentioning
confidence: 99%
“…Brown carbon can be directly emitted from combustion sources 2-4 as part of POA or created by reactions in the atmosphere, such as in the formation or aging of SOA. This secondary brown carbon can be formed from multiple precursors and a variety of reaction pathways, e.g., the reactions of 1,2-dicarbonyls with ammonium (NH 4 + ) salts, 5-10 the aqueous photooxidation of hydroxyacids, [11][12][13] the acid-catalysed condensation of volatile aldehydes, [14][15][16][17][18][19][20][21] and the nitration of aromatic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Acidcatalyzed reaction products were verified using 1 H-NMR analysis similar to that described by Garland et al (2006). Although it was not possible to determine the organic composition of the aerosols in these experiments, the water to sulfate ratio was fortuitously similar to the previous experiments.…”
Section: Ice Nucleationmentioning
confidence: 70%
“…A recent modeling study has investigated the role of dicarboxylic acids in atmospheric ice formation and found that changes in water uptake can affect the size of particles containing organics and thus can explain the observations that organic containing particles are less efficient at ice nucleation (Kärcher and Koop, 2005). While ice nucleation has mainly been studied for mixtures of dicarboxylic acids with ammonium sulfate, other carbonyl-containing compounds, such as aldehydes and ketones, have been investigated at warmer temperatures to probe acid-catalyzed reactions with sulfuric acid (Iraci and Tolbert, 1997;Jang et al, 2002;Nozière and Riemer, 2003;Michelsen et al, 2004;Garland et al, 2006;Liggio et al, 2005;Nozière and Esteve, 2005;Zhao et al, 2005). An important characteristic of these acid-catalyzed reactions is the ability to form products of lower vapor pressure and solubility as well as higher melting points than the initial reactant compounds.…”
Section: Introductionmentioning
confidence: 99%